The Dynamics of Al Wadi'ah Al Mashirifiyyah in Islamic Banking: Theory and Implementation - Feni Anjani; Eka Rodiyah Sri Wulandari; Alfika Safitri; Zaitun Qamariah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This article discusses the dynamics of Al Wadi'ah Al Mashirifiyyah in the context of Islamic banking, with a focus on the theory and implementation of the concept. This literature review explores the origins, basic principles, and practical application of Al Wadi'ah Al Mashirifiyyah in the Islamic banking industry. Through a comprehensive literature analysis, this article evaluates the effectiveness and challenges faced in the implementation of Al Wadi'ah Al Mashirifiyyah. The results of the study show that although this concept offers many benefits, there are also a few challenges in its application that require further attention. This article aims to provide a deep and useful insight for practitioners and academics in the field of Islamic banking.